Biophysical and Biochemical Cues of Biomaterials Guide Mesenchymal Stem Cell Behaviors - Li, Jianjun; Liu, Yufan; Zhang, Yijie; Yao, Bin; Enhejirigala,; Li, Zhao; Song, Wei; Wang, Yuzhen; Duan, Xianlan; Yuan, Xingyu; Fu, Xiaobing; Huang, Sha (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) have been widely used in the fields of tissue engineering and regenerative medicine due to their self-renewal capabilities and multipotential differentiation commitments. However, capitalizing on specific factors to precisely guide MSC behaviors is the footstone of biomedical applications. Fortunately, several key biophysical and biochemical cues of biomaterials that can synergistically regulate cell behavior has paved the way for the development of cell-instructive biomaterials that serve as delivery vehicles for promoting MSC application prospects. Therefore, the identification of these cues in guiding MSC behavior, including cell immigrating, proliferation and differentiation may be of particular importance for better clinical performance. This review focuses on providing a comprehensive and systematic understanding of biophysical and biochemical cues, as well as the strategic engineering of these signals in current scaffold designs, and we believe that integrating biophysical and biochemical cues in next-generation biomaterials would potentially help functionally regulate MSC for diverse applications in regenerative medicine and cell therapy in the future.